The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fpsyt.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Global Negative Effect Expectancies on the Association between Problematic Cannabis Use and Social Anxiety

Abstract: The relationship between social anxiety (SA) and cannabis use among adolescents and young adults is a highly debated topic. In this cross-sectional study, we tested whether cannabis use expectancies mediated the association between SA and cannabis use severity in a sample of 343 young adults (74.3% male) who used cannabis. They completed self-report measures for the screening of problematic cannabis use (Cannabis Use Problems Identification Test) and SA symptoms (Social Interaction Anxiety Scale and Social Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…There is limited and mixed evidence to support social anxiety as a direct predictor of CRNCs. 57 , 58 Social anxiety may moderate the association between social norms and cannabis use problems, 59 and one study reported social anxiety was indirectly associated with cannabis-related problems through solitary use frequency. 60 Social anxiety was also associated with CRNCs via underutilization of protective behavioral strategies (ie, planned behaviors to decrease the use of cannabis) and serial effects with cannabis use frequency and peak quantity 61 as well as the effect on negative and positive affect and sequential effects on frequency of use and problems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited and mixed evidence to support social anxiety as a direct predictor of CRNCs. 57 , 58 Social anxiety may moderate the association between social norms and cannabis use problems, 59 and one study reported social anxiety was indirectly associated with cannabis-related problems through solitary use frequency. 60 Social anxiety was also associated with CRNCs via underutilization of protective behavioral strategies (ie, planned behaviors to decrease the use of cannabis) and serial effects with cannabis use frequency and peak quantity 61 as well as the effect on negative and positive affect and sequential effects on frequency of use and problems.…”
Section: Resultsmentioning
confidence: 99%
“…68 Several cross-sectional studies described an association between higher scores on self-reported impulsivity measures and the experiences of CRNCs. 44,57,[69][70][71] Sensation seekingthe trait of seeking novel and intense experiences-was also significantly associated with CRNCs 45,70,72 with one exception, a significant, negative association to CRNCs among persons with relatively low use of protective behavioral strategies (ie, acting as a mediator for the risk and protective factors of cannabis consequences). 73 There were no longitudinal studies investigating this relationship identified in our search.…”
Section: Intrapersonal Influencesmentioning
confidence: 98%
“…Mammen et al 14 and Hill 12 echoed this result in that cannabis use was often linked with individuals with substance use disorders, which in turn frequently results in higher anxiety levels. For the remaining studies identified, the level of anxiety level reduction/increase was difficult to quantify as every study used a different standard of measuring anxiety (not the GAD-7) 9 , 18 , 36 or utilized primarily surveys/databases to measure anxiety. 13 , 20 , 25 , 37 , 38 Collectively, these data are in contrast to our findings where the vast majority of patients did not show any worsening in their GAD-7 scores or anxiety classification over time.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies, such as Gobbi et al, 16 report that cannabis use is significantly associated with a higher risk for depression, anxiety, and suicide in young adults. However, the majority of former studies are limited due to the following: studies focus on how cannabis increases anxiety levels 12,14,17 rather than how cannabis could potentially improve anxiety 18,19 ; few accurately differentiate cannabis prescribed medically versus non-medical use 13,20 ; studies are typically age-specific with small cohort sample sizes 3,16,[21][22][23][24] ; and the studies primarily measure anxiety and concomitant use of cannabis in the context of other illegal substance use (not medical cannabis use). 25,26 Despite the evidence on its well-validated measure for anxiety, few studies [27][28][29] have directly utilized the generalized anxiety disorder 7-item (GAD-7) 30 questionnaire as a method of measuring anxiety levels in association with cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of consensus of cannabis use for anxiety may also be attributed to the inconsistent nature of the current available literature. Previous studies either tend to strongly focus on the negative effects of cannabis and anxiety (rather than searching for how cannabis may improve anxiety) [ 15 18 ], consist of age-specific and small cohort sizes [ 13 , 19 23 ], did not differentiate cannabis from other illicit substances [ 24 , 25 ], or cannot accurately distinguish cannabis for medical purposes versus recreational where non-medical use which often occur in the context of other drug use [ 26 , 27 ]. Consequently, the current clinical practice guidelines for medical cannabis for Canadian physicians do not support its use for anxiety and other mental health conditions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%